Bulk-like behavior in the temperature driven martensitic transformation of Cu-Zn-Al thin films with 2H structure - Haberkorn, N. (2014)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina